Oral Presentations Abstracts: UTILIZING APPLIED DRAMA IN CLINICAL ETHICS EDUCATION - HATTORI, Kenji (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 We examine the significance and necessity of introducing applied drama into clinical ethics education to build ethics competency. Case-based clinical ethics, distant from abstract theory-based discursive ethics, pays close attention to emotions of persons involved in a given case, and of participants in deliberation. Some authors have sensibly emphasized this point. For example, CURA, a reflective method puts forward the crucial step to become aware of own emotions and physical reactions to each difficult situation. These suggest that we should not stay just in rational reasoning to resolve moral problems in clinical settings. Such a stream seems to lead us to the next stage of clinical ethics education. Applied drama is an umbrella term for the various ways to use theatrical elements, outside of theaters, in educational settings. The basic conception is playing. It includes two meanings: gaming and acting. Generally, we stop playing when we grow up. Applied drama encourages us to play again. Playing promotes communications in verbal and physical. In acting like an acting person, we are to put ourselves in another person’s standpoint. Through acting a role, we may live her life and feel vividly his emotion but by imagination. Thus, applied drama has great potentiality to change the mode of discussion – or deliberation-based clinical ethics. As applied drama comprises various ways such as improvisation, forum theatre, and so on. We will explore their features and application in actual teaching settings.